University of Nigeria, Nsukka, Department of Music. Bulletin 1961-1965 - Edet, Edna M. (International Library of African Music, 1965)
The musical scene in Nigeria today is a study in contrast. The venue may be the concert hall or the village square. The performer may be musically illiterate, semi-illiterate or a graduate from a conservatory or university. The duration of the performance may vary from the three or five minutes spot on NBC or ENTV to the one-week Igue festival of the Benin people. Unity through diversity: This is music in Nigeria today.
Keywords: Music; Ethnomusicology; Education; Nsukka; Nigeria; African Music